Migrasi Internasional dan Pembangunan Daerah: Realitas dan Dualisme Kebijakan Lokal - Haris, Abdul (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2004)
This study was an effort to understand the Sasak people migration phenomena to Malaysia and how those activities were placed in the local development policies This study was also done to understand its contribution in development process. This research was carried out in East Lombok and some sub.districts had been taken as area research sample, such as Pringgasela, Masbagik, Kerrie:1k and Sakra. The sample of research areas were chosen because statistically, were the most potential international migration sources in East Lombok and Lombok island in general. Based on this research, there are three conditions that forte the Sasak people migrate from their area of origin to Malaysia, e.g: poverty, lack of opportuniD4 and low wage compare to destination country. The inability of localgovernment to create new opportunity has become a main factor in all of the migration process. The increasing of employment growth that unbalanced with the growth of opportunity also creates open unemployment and under unemployment at the origin. This fact caused frustration among those of productive age that pushed them to get a better alternative of theirown. The fact also shows that localgovernmentfaced difficulties to put returnees in a clearposition in local development process. This was because there is no regulation that gives possibilities for returnees to involve in all of development process and policy implementation. Migrant participation in a whole development process, therefore, cannot be seen as a program made by government in order to give chance to the returnees directly involved. The other facts show of migrant workers contribution in local economic development. The increasing of economic activities and local treading, workers substitution from farm to non farm are the real phenomenon that can be seen as their contribution in the whole of development process At the macro level, rnigrans contribution has created new opportunity to improve economic activities. This phenomenon may causes that specific group such as labor agents, and